Major orthopedic surgery and its correlation with Cockett syndrome: a case report - Bachir, Raffael Marum; Asaumi, Inácio Diogo; Lo Turco, Donato; Kiyan, Fabio Luiz (Scientific Journal of the Foot & Ankle, 2019)
We report the case of a 42-year-old female patient complaining of pain in the right foot and repetitive sprains for 2 years who underwent surgical repair of pes cavus and ankle ligament reconstruction. Examination images (radiography, nuclear magnetic resonance, and ultrasound), postoperative (PO) period and progression to deep vein thrombosis are presented and discussed, as well as the resolution of this condition by endovascular surgery with angioplasty and stent implantation after suspicion of iliac vein compression syndrome caused by the contralateral iliac artery, known as Cockett syndrome. Level of Evidence V; Therapeutic Studies; Expert Opinion.